2022
DOI: 10.1126/science.abf1970
|View full text |Cite|
|
Sign up to set email alerts
|

Single-cell RNA-seq reveals cell type–specific molecular and genetic associations to lupus

Abstract: Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune disease. Knowledge of circulating immune cell types and states associated with SLE remains incomplete. We profiled more than 1.2 million peripheral blood mononuclear cells (162 cases, 99 controls) with multiplexed single-cell RNA sequencing (mux-seq). Cases exhibited elevated expression of type 1 interferon–stimulated genes (ISGs) in monocytes, reduction of naïve CD4 + T cells that correlated with monocyte ISG expression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
219
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(286 citation statements)
references
References 73 publications
9
219
0
Order By: Relevance
“…We showed that the number of significantly detected co-eQTLs can be greatly increased by either increasing the number of individuals or by increasing the number of cells per individual (Figure 4c, d). believe that future larger single-cell datasets such as two very recent studies (49,50) and the sc-eQTLGen consortium (51) will improve statistical power to identify more robust co-eQTLs. Furthermore, we showed that a sophisticated filtering strategy of tested SNP-genegene triplets is essential to maximize the number of reliable co-eQTLs.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the number of significantly detected co-eQTLs can be greatly increased by either increasing the number of individuals or by increasing the number of cells per individual (Figure 4c, d). believe that future larger single-cell datasets such as two very recent studies (49,50) and the sc-eQTLGen consortium (51) will improve statistical power to identify more robust co-eQTLs. Furthermore, we showed that a sophisticated filtering strategy of tested SNP-genegene triplets is essential to maximize the number of reliable co-eQTLs.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies 11 and large-scale single cell RNA sequencing analysis 12 confirmed the inverse association between type I IFN activity and the abundance of circulating lymphocytes or naïve CD4 + T cells in SLE patients. However, the type I IFN signaling pathway in CD4 + T cells remains incompletely understood and it is unclear how type I IFN overactivation may be linked to T cell lymphopenia in lupus.…”
Section: Introductionmentioning
confidence: 86%
“…The prevailing theory on the pathogenesis of the lymphopenia in lupus has been centered on antilymphocyte antibodies 51 . But a large-scale multiplex single cell RNA-seq analysis demonstrated a clear inverse correlation between type I IFN activity and circulating naïve CD4 + T cells in SLE patients 12 . Our study corroborates with such observation indicating that elevated type I IFN production may be another contributing factor for the lymphopenia phenotype in lupus partly by potentiating mTORC2 activation.…”
Section: It Has Long Been Established That Exuberant Type I Ifn Activ...mentioning
confidence: 97%
“…Recently, Perez et al. also reported larger-scale single-cell RNA-seq profiles (>1.2 million single cells) in the PBMC of 162 SLE patients and healthy controls both from European and Asian ancestries ( 15 ). They revealed a reduction in naïve CD4 + T cells and an increase of GZMH + CD8 + T cells in SLE.…”
Section: Single-cell Rna-seq Of Blood Immune Cells In Slementioning
confidence: 99%
“…Also, using single-cell RNA-seq data of SLE patients, Perez et al. performed eQTL analysis in the eight most abundant cell types ( 15 ). Their analysis identified 3331 genes with at least one eQTL in a cell type.…”
Section: Dynamic Eqtl Analysis Of Autoimmune Diseasesmentioning
confidence: 99%